2018
DOI: 10.1136/bmjopen-2017-019554
|View full text |Cite
|
Sign up to set email alerts
|

Perinatally acquired HIV-positive status disclosure and associated factors in Dire Dawa and Harar, Eastern Ethiopia: a health facility-based cross-sectional study

Abstract: ObjectivesThe aim of this study was to assess the level and factors associated with caregivers’ disclosure of perinatally HIV-infected (PHIV+) children’s seropositive status.DesignWe conducted a cross-sectional study in five public health facilities providing HIV treatment and care in Dire Dawa and Harar, Eastern Ethiopia. The data were collected from 310 caregivers through face-to-face interviews and record reviews. Data analyses were done using STATA V.14.2 and statistical significance was declared at p valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
8
22
0
Order By: Relevance
“…The same finding was reported previously in the study in Eastern and North-East part of Ethiopia [16] [ 22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The same finding was reported previously in the study in Eastern and North-East part of Ethiopia [16] [ 22].…”
Section: Discussionsupporting
confidence: 91%
“…Even though studies claim that informing children about their HIV status has long term positive implications in HIV disease management, children's quality of life and ART drug adherence, In many parts of the Sub-Saharan African Countries, the HIV status disclosure reaches from 0 to 69.2% [8].For instance, the HIV status disclosure reaches 26% -33% in Kenya [9], 32.6% in Uganda [10], 22.3% in Tanzania [11], 40% in South Africa [12], with the age at disclose reaching from 5 to 15 years [13]. In the Democratic Republic of Congo, nearly 50% of children didn't know their status while 15% partially informed.…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to the 26% reported by Vreeman et al in Kenya [4], 22.3% by Mumburi et al in Tanzania [10] and 21% by Kallem et al [11] in Ghana but higher than 14% in a study by Arun et al in India [12]. It was however lower than 33.1%, reported by Gyamfi et al [2], 49.4% by Mengesha et al [13], 43.1% by Lester et al [14] and 39.6% by Madiba et al [15] in South Africa.…”
Section: Discussionsupporting
confidence: 86%
“…The mean age at disclosure was 14 years which was older than in other reports [10,13,17]. The mean age at disclosure was 10.6 years in a study by Mumburi et al in Tanzania [10]; 8.7 years in a Nigerian study by Brown et al [17] and 11.2 years in Ethiopia [13].…”
Section: Discussionmentioning
confidence: 61%
“…According to one systematic review,in low-and middle-income countries the overall rate of HIV-positive status disclosure to HIV-infected children was low, which ranges from 1.7% to 41% [11]. Fewer studies, conducted in different cities of Ethiopia, showed that children who knew their HIV positive status were low, which ranges from 16.3% to49% [12][13][14][15][16][17][18]. As children mature, however, lack of disclosure may lead to accidental disclosure.…”
Section: Introductionmentioning
confidence: 99%